3D‐printed reflector antenna and metallization in Ka‐band. Issue 6 (18th February 2022) - Guo, Liwei; Li, Simin; Jiang, Xing; Liao, Xin; Zhang, Ying; Shi, Bin
Abstract: A novel high precision and lightweight reflector antenna is proposed. The fabrication process of the reflector adopted Stereo Lithography Apparatus (SLA) printed and metallization. The proposed SLA Reflector (SLAR) antenna structure adopts three‐dimensional‐printed, which can design complex geometric shapes flexibly and rapid prototyping. That is a good substitute for the traditional method of millimeter wave reflector processing. In order to realize radio frequency (RF) characteristics perfectly, the metallization process of photosensitive resin was elaborated, which realized by first electroless nickel plating, then copper electroplating, and finally chromium electroplating on the protective layer. For verification, the designed reflector antenna was manufactured and measured. The reflectivity of SLAR was measured well by the bow method, which validates excellent fabrication accuracy and reliability. The gain and pattern were measured in the anechoic chamber. The results show that the proposed reflector antenna achieves the gain of 25 dBi and the 3 dB gain bandwidth of 43% over the full Ka‐band. A good agreement can be observed between measurement and simulation.